Massacre on the Gila An Account of the Last Major Battle Between American Indians, with Reflections on the Origin of War - Kroeber, Clifton B. (University of Arizona Press, 2019)
"The careful reconstruction of the September 1, 1857 battle at Maricopa Wells, combined with the thorough and well-written summary of available information on patterns of regional conflict, makes this book a valuable contribution to the ethnohistory of the middle Gila and Lower Colorado River area." -American Anthropologist "Rarely do the skills of historians and anthropologists mesh so admirably." -Western Historical Quarterly "Kroeber and Fontana are meticulous professionals. Their study of this neglected slice of Southwestern history deserves applause." -Evan S. Connell, Los Angeles Times Book Review "A rich feast for the curious and theorist alike." -Pacific Historical Review "Kroeber and Fontana describe a little-known event, provide an effective analysis of the cultures of Indian groups in southwestern Arizona, and attempt to understand the broader causes of warfare. The result is an interesting and provocative study." -Journal of American History